Analisis Kebutuhan Pengembangan Buku Suplemen Menulis Deskriptif Berbasis Observasi Lingkungan Pada Siswa Sekolah Dasar - Luh Ketut Ari Utami; I Ketut Suparya; Ni Nyoman Lisna Handayani (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the need for developing a supplementary book for descriptive writing based on environmental observation for elementary school students. The problem underlying this study is the low quality of students’ descriptive writing, particularly in terms of content development, text organization, and the use of concrete descriptive vocabulary. This research employed a research and development approach with a focus on the needs analysis and preliminary study stage. The study was conducted with sixth-grade students from an elementary school cluster in Tabanan District, involving 72 students and 4 classroom teachers. Data were collected through document analysis of students’ written work, classroom observations, teacher interviews, and a student needs analysis questionnaire. The findings indicate that most students have not achieved mastery in content and language aspects, while descriptive writing instruction in the classroom is still dominated by textbook-based approaches without systematic environmental observation activities. In addition, both teachers and students expressed the need for supplementary teaching materials that can guide the writing process in a structured and contextual manner. The scientific contribution of this study lies in positioning needs analysis as an empirical foundation for designing a descriptive writing supplementary book grounded in the local environmental context and aligned with experience-based learning principles within the Merdeka Curriculum framework.